PENGARUH PROFITABILITAS, LIKUIDITAS, FIRM SIZE DAN PPh TERHADAP NILAI PERUSAHAAN - Feni Erma Wijayanti; Jeni Susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe purpose of this research is to determine the effect of profitability, liquidity, firm size and tax rate to firm value food and beverage sub-sector listed in Indonesia Stock Exchange period 2014-2018. The population taken in this research is 18 companies and sample used 11 companies. The sampling technique used in this research is purposive sampling method, where sample methods selection is based on certain criteria. The analysis method has been conducted by using multiple linear regressions analysis and the application instrument the SPPS (Statistical Product and Services Solutions). The results of this research indicate that: 1) Profitability (return on assets) has a positive and significant effect on firm value (price to book value) 2) Liquidity (current ratio) has a negative and not significant effect on firm value (price to book value) 3) Firm Size (Size) has a positive and not significant effect on firm value (price to book value) 4) PPh has a positive and significant effect on firm value (price to book value).Keywords: profitability, liquidity, firm size, tax rate, firm value